Pengenalan Teknologi Penyediaan Bibit Berkualitas Multi Entris Untuk Percepatan Perolehan Produksi Tinggi Tanaman Jarak Pagar Dalam Rangka Pengembangan Desa Mandiri Energi Ramah Lingkungan - Bambang Budi Santoso; I Gst. Md. Arya Parwata; I Nym. Soemeinaboedhy (Jurnal Gema Ngabdi, 2019)
Jatropha plants in the Amor-Amor area, North Lombok Regency, West Nusa Tenggara have long been growing and developing as land boundaries, yards, and village roads, but are not used as alternative energy sources, then they do not provide results or income. This is due to limited ability to apply technology for create more profitable. On the other side, utilization of irrigation facilities that have been provided in the form of bore-wells is very rarely used in connection with expensive operational costs, especially on fuel components. Extension activities and demonstrations in the provision of multi-entry Jatropha seedlings with the aim of increasing the knowledge of farmer group members for better implementation Jatropha cultivation technology. The results show that the counseling and demonstration provided was quite capable of arousing interest and the need for farmers to adopt introduced technology. Members of the Telaga Valley Farmers Group were at the trying stage and if assistance is continued, farmers will reach the adoption phase, therefore it takes a long time for technology transformation to form an Energy Independent Village